THE EFFECT OF THE PEDAGOGICAL AND TEACHERS' PERSONALITY COMPETENCIES ON THE FORMATION OF LOVING-KINDNESS CHARACTER AMONG BUDDHIST JUNIOR HIGH SCHOOL STUDENTS IN TEMANGGUNG REGENCY: PENGARUH KOMPETENSI PEDAGOGIK DAN KEPRIBADIAN GURU TERHADAP PEMBENTUKAN KARAKTER CINTA KASIH PESERTA DIDIK BUDDHIS SEKOLAH MENENGAH PERTAMA DI KABUPATEN TEMANGGUNG - Musini, Musini; Sukodoyo, Sukodoyo; Setyaningsih, Setyaninsih (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2019)
The aim of this research to determine the effect of the pedagogical and teachers' personality competencies on the formation of loving-kindness character among Buddhist junior high school students in Temanggung regency. The research method used ex post facto. The research samples totaling 156 students taken by simple random sampling. The data collection used questionnaires. The validity instrument is calculated using product moment formula and the reliability test uses Alpa Cronbach formula. Data research was analyzed using multiple linear regression. The results of the research showed there was a significant influence in the formation of loving-kindness character among junior high school Buddhist students in Temanggung regency through pedagogical competence and personality of the teacher. This is indicated by sig value. 0,00 < 0,05. The magnitude contribution pedagogical competence and teacher's personality to the formation of loving-kindness is 20,8% and the regression line equation is Y = 14.588 + 0.476 X1 + 0.424 X2. Penelitian ini bertujuan untuk mengetahui pengaruh kompetensi pedagogik dan kepribadian guru terhadap pembentukan karakter cinta kasih peserta didik Buddhis SMP di Kabupaten Temanggung. Metode penelitian yang digunakan ex-post facto. Sampel penelitian berjumlah 156 peserta didik yang diambil dengan simple random sampling. Pengumpulan data dengan menggunakan angket. Validitas instrumen dihitung menggunakan rumus product moment dan uji reliabilitas menggunakan rumus Alpa Cronbach. Data penelitian ini dianalisis menggunakan regresi linear berganda. Hasil penelitian menunjukkan ada pengaruh yang signifikan dalam pembentukan karakter cinta kasih peserta didik Buddhis SMP di Kabupaten Temanggung melalui kompetensi pedagogik dan kepribadian guru. Hal ini ditunjukkan dengan nilai sig. 0,00 < 0,05. Besarnya sumbangan dari kompetensi pedagogik dan kepribadian guru terhadap pembentukan karakter cinta kasih sebesar 20,8% dan persamaan garis regresinya Y = 14,588 + 0,476 X1 + 0,424 X2.